2017
DOI: 10.1155/2017/2045157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salinity Intrusion on Food Crops, Livestock, and Fish Species at Kalapara Coastal Belt in Bangladesh

Abstract: Salinity has caused significant negative effects on agricultural production. This research is focused on the vulnerabilities of soil and water salinities on crop, fish, and livestock production across the Kalapara coastal belt of Bangladesh. Several parameters were measured as indicators of salinity. The electrical conductivity of water was found to be significant with TDS, F−, Cl−, SO42-, Na+, K+, Ca2+, Mg2+, NO2-, and PO43-. Chloride was found to be identical with SO42-, Na+, K+, Ca2+, Mg2+, Br−, and PO43-. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(94 citation statements)
references
References 36 publications
6
88
0
Order By: Relevance
“…Therefore, about a 70% increase in food production is required within 30 years. But, the salinization problem contributes to a loss of 12 billion US dollar per year [5][6][7], which ultimately undermines the goal of meeting global food security [8]. Salinity stress provokes a wide array of responses in plants via affecting its morpho-physiological, biochemical, and molecular processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, about a 70% increase in food production is required within 30 years. But, the salinization problem contributes to a loss of 12 billion US dollar per year [5][6][7], which ultimately undermines the goal of meeting global food security [8]. Salinity stress provokes a wide array of responses in plants via affecting its morpho-physiological, biochemical, and molecular processes.…”
Section: Introductionmentioning
confidence: 99%
“…From that massive area, a 0.83 million hectare region is severely devastated by salinity which is 30% of the entire cultivable land of Bangladesh. Estimation shows that the extent of salt-affected areas has increased by nearly 26.0% in the coastline of Bangladesh in the last 35 years [8,48]. Moreover, the soil salinity in the dry season is three times higher than that of the rainy season, and it is possible to minimize the salinity level of the surface soil by intensifying crop production during this time [49].…”
Section: Introductionmentioning
confidence: 99%
“…All these findings indicated that the isolated strains were rhizobial strains [19][20][21] . Salinity intrusion has a common effect on food crops, livestock, and fish species of Bangladesh and the response to such stress are diverse in microbial community 22 . In addition to that, response to other stress like temperature, pH, and antibiotics are highly variable among the rhizobial species 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Seawater intrusion leads an increase in the salinity of water in irrigation systems and reduces the yield of food crops such as paddy rice and maize [82]. Saline water intrusion increases soil and water salinity, promoting a shortage of grazing land and fodder crops for livestock production, as well as eliminating fresh fish species in the surface water aquifer [83]. At a larger scale, seawater intrusion on agricultural land leads to a change in rice cropping systems and land use patterns [84].…”
Section: Future Perspectivesmentioning
confidence: 99%